PENGARUH LIQUID STATE FERMENTATION TERHADAP PERTUMBUHAN TANAMAN TOMAT - Lestari, Pertiwi Indah; -, Rahman (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2019)
LSF (Liquid State Fermentation) is a liquid organic fertilizer that is fermented to obtain nutrients for plants. This study aimed to find out the effects of supplying towards the growth of tomato plant and the concentration of the liquid organic fertilizer of coconut water and tajin water which was the most optimal in the growth of tomato plant. This study was done experimentally using Completely Randomized Design (CRD) with one factor and three groups in the liquid coconut water and tajin water, each group consisted of four repetitions. The dependent variable in this study was the concentration of liquid organic fertilizer of coconut water and tajin water which was 100 ml, 150 ml, 200 ml. The Anova is used as data analysis test method to analysis the plant height, and number of leaf. Based on statistic test, the conclusion is the concentration of liquid organic fertilizer of coconut water and tajin water which is different can cause the various growths of tomato. In the concentration 100 ml, the liquid organic fertilizer of coconut water and tajin water is the most optimal dose with average of number the height (31,05 cm) and number of leaf (29,23 leaf) of tomato plant (Solanum lycopersicum L.).